Post-weaning infant-to-mother bonding in nutritionally independent female mice. - Stijn Stroobants; John Creemers; Guy Bosmans; Rudi D'Hooge (PLoS ONE)
Infant-parent attachment is highly selective and continues beyond essential care in primates, most prominently in humans, and the quality of this attachment crucially determines cognitive and emotional development of the infant. Altricial rodent species such as mice (Mus musculus) display mutual recognition and communal nursing in wild and laboratory environments, but parental bonding beyond the nursing period has not been reported. We presently demonstrated that socially and nutritionally independent mice still prefer to interact selectively with their mother dam. Furthermore, we observed gender differences in the mother-infant relationship, and showed disruption of this relationship in haploinsufficient Nbea+/- mice, a putative autism model with neuroendocrine dysregulation. To our knowledge, this is the first observation of murine infant-to-mother bonding beyond the nursing period.